SAT0160 Prediction of Remission and Low Disease Activity in Dmard-Refractory Patients with RA Treated with Golimumab. (9th June 2015) - Vastesaeger, N.; Durez, P.; Dasgupta, B.; Combe, B.; Schulze-Koops, H.; Louw, I.; Wollenhaupt, J.; Zerbini, C.A.F.; Beaulieu, A.; Pavelka, K.; Lazaro, M.; Garcia Kutzbach, A.; et al.
Abstract : Background: EULAR recommendations for RA therapy suggest addition of a biologic only if poor prognostic factors such as high disease activity are present. However, low baseline disease activity is associated with better biologic treatment outcomes. Objectives: To develop a tool to predict remission/low disease activity (LDA) and aid in selection of patients for anti-TNF treatment. Methods: GO-MORE was an open-label, multinational, prospective study in biologic-naïve patients (pts) with active RA despite DMARD therapy. Pts received 50-mg subcutaneous golimumab (GLM) once monthly for 6 months along with their background DMARDs. Predictors of 28-joint disease activity score based on ESR (DAS28-ESR) LDA and remission at 6 months were evaluated with univariate and multivariable regression models and receiver operating characteristic (ROC) analyses. To assess the relationship between predicted disease states and observed amount of improvement, further analyses evaluated associations between the final regression model's predicted rate of remission and observed 6-month improvements in DAS28, Health Assessment Questionnaire (HAQ), and EurolQoL 5-Dimension (EQ-5D). Results: 3280 pts were included in the analysis: 82.8% female, mean age 52.3 years, mean disease duration 7.6 years, mean baseline DAS28–ESR 5.97 (standard deviation=1.095). DAS28-ESR remission and LDA were achieved by 23.9% and 37.4% of pts, respectively, after 6 months of GLM therapy. In multiple regression models, remission at 6 months was associated with male sex, absence of comorbidities, and lower age, HAQ, ESR, and tender joint count-28 (TJC28). The final model included sex, comorbidities, age, HAQ, ESR, and TJC28 as continuous variables and had an area under the ROC curve of 0.71 to predict remission and LDA at 6 months. When CRP replaced ESR or SJC28 replaced TJC28, predictive ability was slightly reduced. Predicted remission rates ranged from 4% to 67% in females (figure ) and from 7% to 76% in males. Patients who were predicted to be least likely to reach DAS28 remission (who also had the highest baseline disease activity) had the greatest improvements in DAS28, HAQ, and EQ-5D scores during 6 months of GLM treatment. Conclusions: Baseline sex, age, ESR, HAQ, absence of comorbidities, and TJC28 were predictive of remission and LDA after 6 months of GLM treatment. Patients with lower likelihood of remission still experienced improvements in DAS28, HAQ, and EQ-5D during treatment. Disclosure of Interest: N. Vastesaeger Employee of: MSD Belgium, Brussels, Belgium, P. Durez: None declared, B. Dasgupta Grant/research support from: EULAR, ACR, Health Technology Assessment, British Heart Foundation, Research for Patient Benefits UK, Napp, Consultant for: Schering Plough, Merck, Roche, Mundipharma, Astra Zeneca, B. Combe Consultant for: Merck, H. Schulze-Koops Consultant for: Abbott, Actelion, Biotest, BMS, Chugai, Essex, GSK, MSD, Medac, Merck, Mundai Pharma, Novartis, Nycomed, Pfizer, Roche, UCB, I. Louw Grant/research support from: Merck, BMS, Pfizer, Roche, Janssen, and Lilly, Consultant for: Abbott, BMS, Janssen Pharmaceutica in South Africa, the Merck Investigator Consulting Network, J. Wollenhaupt Grant/research support from: AbbVie, UCB, Pfizer, Sanofi, Astra Pharma, Consultant for: MSD, C. A. Zerbini Grant/research support from: Novartis, Pfizer, Bristol, Lilly, Amgen, MSD, Consultant for: Pfizer, Bristol, Lilly, MSD, A. Beaulieu Grant/research support from: Merck, Servier, Novartis, Amgen, Abbott, Pfizer, Eli Lilly, Roche Centocor, Centocor, Celgene, AbbVie, UCB, Arthrolab, K. Pavelka Consultant for: Amgen, Roche, BMS, MSD, UCB, M. Lazaro Grant/research support from: Bristol Myers Squibb Argentina, Consultant for: Abbott Laboratories, MSD, A. Garcia Kutzbach Grant/research support from: Merck, Janssen, Lilly, Sanofi, Astra Zeneca, R. Moots: None declared, H. Amital: None declared, S. Huyck Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, B. Fu Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, M. Govoni Employee of: MSD Italy, Rome, Italy